2022
DOI: 10.11646/palaeoentomology.5.2.9
|View full text |Cite
|
Sign up to set email alerts
|

New dictyopteran fossils from the Pennsylvanian of West Beijing, China

Abstract: Carboniferous insects from China are rare. Here we report a new fossiliferous locality at the Yexi Section, western Beijing, from where Pennsylvanian insects have been discovered. These insect fossils collected from the black shales of the Benxi Formation (middle–late Moscovian to early Kasimovian) are associated with rich plant remains. The fossils are represented mainly by dictyopteran tegmina that cannot be further identified. The discovery is helpful for our understanding of the diversity and preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…We counted 10 items, but the data showed that the data of 4 items were relatively complete and had a clear trend (Table 1). The specific performance is: [21] 2 genus P2 Yinping Anhui Fu et.al.,2021 [22] 2 [23] 8 genus 5 genus T2 Tongchuan Shannxi Zhao, 2020 [18] Proto-Orthoptera distributed 2 genera, 1 genus and 1 genus in Shanxi, Henan and Anhui in the middle of the North Permian period, respectively, and 6 genera in Ningxia in the early Triassic period, which showed that the overall performance was that the Permian had a decreasing trend, but the diversity of the early Triassic suddenly increased significantly. It is not distributed in South China (Fig.…”
Section: Data Analyses and Resultsmentioning
confidence: 99%
“…We counted 10 items, but the data showed that the data of 4 items were relatively complete and had a clear trend (Table 1). The specific performance is: [21] 2 genus P2 Yinping Anhui Fu et.al.,2021 [22] 2 [23] 8 genus 5 genus T2 Tongchuan Shannxi Zhao, 2020 [18] Proto-Orthoptera distributed 2 genera, 1 genus and 1 genus in Shanxi, Henan and Anhui in the middle of the North Permian period, respectively, and 6 genera in Ningxia in the early Triassic period, which showed that the overall performance was that the Permian had a decreasing trend, but the diversity of the early Triassic suddenly increased significantly. It is not distributed in South China (Fig.…”
Section: Data Analyses and Resultsmentioning
confidence: 99%
“…In the early 1980s, Ye Junlin et al revisited the cave and compared the new measurement data with the old data. Huang Wanbo et al also visited the cave to study the formation of vertebrate fossils [15]. The Yunshui Cave in Shangfang Mountain is a place of high cultural and scientific value.…”
Section: Introductionmentioning
confidence: 99%